An electrochemically controlled supramolecular zip tie based on host–guest chemistry of CB[8]. Issue 27 (30th June 2020) - Neira, Iago; Domarco, Olaya; Barriada, Jose L.; Franchi, Paola; Lucarini, Marco; García, Marcos D.; Peinador, Carlos
Abstract : A stimuli-responsive supramolecular assembly based on a bipyridinium thread and CB[8] behaves like a zip tie relaxing the chain as a consequence of the insertion of both radical cation moieties within the CB[8] macrocycle. Abstract : Three molecular threads incorporating two viologen units attached by an oligo-ethylene glycol chain of variable length and an electron rich naphthalene moiety were prepared. The internal viologen unit is connected to the naphthalene by a rigid linker that prevents the simultaneous complexation of these systems. The axle with the shortest chain (1 4+ ) in the presence of CB[8] placed the chain inside the macrocycle in aqueous media. In contrast, the longer chains in 2 4+ and 3 4+ allow locating the terminal viologen and the electron rich unit inside the cavity. Upon reduction of the bipyridinium salts, the system behaves like a zip tie relaxing the chain as a consequence of the insertion of both radical cation moieties within the CB[8] and making these switches as potential components for molecular machinery.